Control-Shift: Censorship and the Internet - Crawford, Kate (Remote Control: New Media, New Ethics, eds. Catharine Lumby and Elspeth Probyn, 2006)
This analysis of the ethical challenges posed by new media formats, technologies and audiences considers many aspects of these emerging genres and technologies. It reveals how they work and are reshaping the public sphere, as well as how the connections between product and viewer, and producer and media consumer, are being changed by new shows and formats. With so much interest in contemporary media forms and so many heated debates about media ethics, this book is essential to journalists, media practitioners and theorists.